2022
DOI: 10.1002/er.7778
|View full text |Cite
|
Sign up to set email alerts
|

Geothermal resources for sustainable development: A case study

Abstract: Summary Turkey's primary energy source is fossil fuels, with a contribution of 55%. According to the International Energy Agency forecast, fossil fuels will continue to be the primary energy source for the next decade. The current CO2 emissions from fossil fuel‐based energy are 400 Mt. If the present energy usage trend continues, then the emissions will cross 500 Mt by 2030. However, Turkey has large scope to mitigate climate‐related issues and follow sustainable development agenda by increasing the share of g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…In the case of EGS energy source, currently, EGS is in its development stage and being adopted by several countries (France, Australia, Germany, China, UK, and USA) due to the availability of high radiogenic granites (Koelbel and Genter 2017 ; Breede et al 2013 ; Pan et al 2019 ; Somerville et al 1994 ; Ledingham et al 2019 ; Cooper et al 2010 ; Chandrasekharam and Baba 2021 ; Baba and Chandrasekharam 2022 ). The Levelized Cost of electricity generated from EGS sources is currently higher than the other energy sources (Table 3 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the case of EGS energy source, currently, EGS is in its development stage and being adopted by several countries (France, Australia, Germany, China, UK, and USA) due to the availability of high radiogenic granites (Koelbel and Genter 2017 ; Breede et al 2013 ; Pan et al 2019 ; Somerville et al 1994 ; Ledingham et al 2019 ; Cooper et al 2010 ; Chandrasekharam and Baba 2021 ; Baba and Chandrasekharam 2022 ). The Levelized Cost of electricity generated from EGS sources is currently higher than the other energy sources (Table 3 ).…”
Section: Discussionmentioning
confidence: 99%
“…This cost does not exist in the case of electricity generated from the geothermal energy source. Thus, electricity generated from geothermal energy sources is much cheaper compared to the electricity generated from fossil fuels energy sources (Ikram 2021 , Baba and Chandrasekaram, 2022 ). In addition to the future cost reduction due to advancement in drilling technology, the advantage that Turkey (western Anatolian region) has is the presence of Curie depth point at shallower depth (~ 12 km) and high heat flow values over the entire region (Akin et al 2014 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Baba and Chandrasekharam ( 2022 ) found that direct geothermal heating of homes and hotels in Turkey utilizes 2339 MWt of heat, resulting in a 40% reduction in carbon dioxide emissions. In Pratiwi and Trutnevyte ( 2021 ) study, geothermal energy was combined with waste incineration and natural gas boilers to replace 50% of the natural gas consumption, leading to a significant decrease of 60% in greenhouse gas emissions.…”
Section: Green Solutions For Home Heatingmentioning
confidence: 99%
“…2). Although the RHP of the granites of western Anatolia is lower than that of Saudi Arabian granites, the advantage Turkey has is the disposition of high-temperature isotherm (Curie point temperature-depth) at a very shallow depth (6 to 12 km [1,3] and a foundered continental and thinned crust due to the Alpine-Himalayan orogeny.…”
mentioning
confidence: 99%